Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fnins.2022.854422
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Spatial and Temporal Patterning in the Invertebrate and Vertebrate Nervous System

Abstract: The nervous system is one of the most sophisticated animal tissues, consisting of thousands of interconnected cell types. How the nervous system develops its diversity from a few neural stem cells remains a challenging question. Spatial and temporal patterning mechanisms provide an efficient model through which diversity can be generated. The molecular mechanism of spatiotemporal patterning has been studied extensively in Drosophila melanogaster, where distinct sets of transcription factors define the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 133 publications
1
5
0
Order By: Relevance
“…Consistent with the NT-type results, the markers for the cell types present in the diencephalon, mid- and hindbrain at E14.5 were differentially expressed in clusters (Figure 4). The final number of scATAC-seq cell clusters (n=189) matches well with the expectation to find the 6 neuron classes as well as the neuronal progenitors, while each neuron type can be present in several stages of neurogenesis and maturation in E14.5 mouse brain, which is further divided into dorso-ventral (7 domains) and anterior-posterior (4-5 domains) molecularly distinct domains and may give rise to temporal sublineages 2527 . Importantly, the categorization by neurotransmitter identity reveals broad classes of neurons, while distinguishing the whole range of molecular identities would require an improved set of markers.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with the NT-type results, the markers for the cell types present in the diencephalon, mid- and hindbrain at E14.5 were differentially expressed in clusters (Figure 4). The final number of scATAC-seq cell clusters (n=189) matches well with the expectation to find the 6 neuron classes as well as the neuronal progenitors, while each neuron type can be present in several stages of neurogenesis and maturation in E14.5 mouse brain, which is further divided into dorso-ventral (7 domains) and anterior-posterior (4-5 domains) molecularly distinct domains and may give rise to temporal sublineages 2527 . Importantly, the categorization by neurotransmitter identity reveals broad classes of neurons, while distinguishing the whole range of molecular identities would require an improved set of markers.…”
Section: Resultssupporting
confidence: 78%
“…Here, the topology of the cell type tree can provide a measure of developmental and evolutionary relatedness of cell types 35 : Specific patterns of genomic feature expression - or enhancer use - along the branches of a cell type tree can reveal genetic regulatory logic. For example, it has been shown that neurotransmitter phenotype can be associated with multiple TF combinations in Drosophila and C. elegans , and that the expression pattern of neural differentiation genes are better explained by a model where each gene can be regulated by several TFs 6,7 . The examples of such phenotypic convergence are still rare in vertebrates, however the divergence between lineage relatedness and final acquired cellular phenotype has been demonstrated in zebrafish lineage tracing studies 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Some patterning genes are expressed at distinct time points from the generation of neurons while still influencing the type of daughter cell generated, indicating transcriptional memory ( Erclik et al, 2017 ; Konstantinides et al, 2022 ). It has been proposed that unique chromatin states exist in neuroblasts expressing the same transcription factors ( Chen and Konstantinides, 2022 ; El-Danaf et al, 2023 ; Janssens et al, 2022 ; Rossi et al, 2021 ; Sen, 2023 ). Although there is support for a model of chromatin state heterogeneity, how these are generated and maintained remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal transcription factor series have been described in different contexts [48], but nowhere nearly as comprehensively as in the Drosophila developing optic lobe [49,50]. As mentioned earlier, the transcription factors that are expressed temporally in the Drosophila ventral nerve cord neuronal stem cells are also expressed along the AP axis of the blastoderm embryo like gap genes (Fig.…”
Section: Evolution Of Spatial From Temporal Patternsmentioning
confidence: 99%